2003
DOI: 10.1016/s1010-7940(03)00188-x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and long-term results of mitral prosthetic replacement using a right thoracotomy beating heart technique

Abstract: Mitral prosthetic replacement via a right thoracotomy on beating heart under normothermic bypass offers a safe alternative to redo median sternotomy in this high-risk group. Operative access is facilitated and procedural time reduced. Complication rates are low and perioperative mortality is lower than that generally reported with conventional surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
79
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 8 publications
3
79
1
2
Order By: Relevance
“…5 Indeed, Thompson et al reported excellent results in 125 patients (22 patients with previous CABG) who underwent mitral valve replacement using a right thoracotomy beating heart technique. 17 We mainly used cardiac arrest and systemic cooling in the present study and were satisfied with the cardiac outcome as evidenced by the absence of perioperative infarction. Byrne et al reported similar results in 21 patients operated on via right anterolateral thoracotomy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…5 Indeed, Thompson et al reported excellent results in 125 patients (22 patients with previous CABG) who underwent mitral valve replacement using a right thoracotomy beating heart technique. 17 We mainly used cardiac arrest and systemic cooling in the present study and were satisfied with the cardiac outcome as evidenced by the absence of perioperative infarction. Byrne et al reported similar results in 21 patients operated on via right anterolateral thoracotomy.…”
Section: Discussionmentioning
confidence: 93%
“…An anterolateral right thoracotomy avoids the dissection of patent grafts, thereby reducing operative risk. 16,17 However, a possible downside of this approach may be the risk for suboptimal myocardial protection. This is why 2 patients underwent a hybrid approach.…”
Section: Discussionmentioning
confidence: 99%
“…It also decreases the potential damage risk to cardiac tissue and main vascular tissue, especially the right ventricle. Valve disease in patients with patent grafts and in no need of CABG could be served by RAMT as well (10). Patients in the RAMT group easily recovered because of their relatively intact thoraxes that offered earlier mobilization and return to the activities of daily life.…”
Section: Discussionmentioning
confidence: 99%
“…Complication rates are low and perioperative mortality was shown to be lower than that generally reported with conventional surgery. 44) Minimally invasive mitral valve reoperations, which were performed in 181 consecutive patients by right-sided lateral minithoracotomy with femoral cannulation for CPB is a useful alternative for patients requiring a mitral valve procedure after previous cardiac surgery, particularly in patients with patent coronary bypass grafts or previous AVR. 45) Port-access video-assisted right mini-thoracotomy also allows for good results in a difficult subset of patients.…”
Section: Redo Mitral Valve Replacementmentioning
confidence: 99%